Permeability of Two Clayey Soils Exposed to Petroleum Products and Organic Solvents - Mehran Karimpour-Fard; Roghayeh Alimohammadi-jelodar (Civil Engineering Infrastructures Journal, 2018)
Clayey soils are the most common material used for water sealing and undertake an important role in controlling landfill-related pollution. Organic liquids can adversely affect the effectiveness of clay liners by drastically increasing their hydraulic conductivity. The aim of this study is to investigate and compare the permeability in two types of clay with different plasticity, exposed to the flow of kerosene and diesel as non-polar immiscible liquids and ethanol as a miscible liquid with an intermediate dielectric constant. The effects of plasticity and water content for a given compactive effort are also investigated. Two different clayey soils with different plasticity were provided and their physical properties determined. Next, modified constant-head permeability tests were conducted on the samples. Results show that the lower dielectric constant of the organic fluids, leads to an increase in hydraulic conductivity. Research has shown that organic fluids shrink the diffuse double layer due to their lower dielectric constant and reduce its thickness. Shrinkage of the double layer leads to higher permeability and lower plasticity in the soil. As a result, the void space for the passage of the fluid increases. With the decrease the dielectric constant from 80.1 to 1.8, permeability is increased up to 1800 times. On the other hand, results show that for a clay with a higher liquid limit and plastic limit, permeability for all the liquids investigated in the research is lower.